2008
DOI: 10.1016/j.mambio.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Transition of nonharem male to harem male status in the short-nosed fruit bat Cynopterus sphinx

Abstract: The short-nosed fruit bat Cynopterus sphinx is known to exhibit resource defence polygyny as its primary mating strategy. Tent construction by harem males to recruit females represents a heavy investment of time and effort, which is not done by nonharem males. The previously unobserved mode of harem formation by the solitary males was studied using mark-recapture and radio-telemetry. In our observation, the solitary males roosting near to harems started recruiting females by occupying the tent abandoned by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(59 reference statements)
3
10
0
Order By: Relevance
“…Harem groups are relatively unstable in C. sphinx. Thus such association can be explained as an extension of male-female association, as these non-harem males are known to achieve harem status as well (Karuppudurai et al, 2008;Storz et al, 2000), and such an event could have a consequence on the overall relatedness in the harem and the colony and might as well be a reflection of possible cryptic mate choice, a possibility already suggested by Campbell (2008).…”
Section: Relatedness Between Colony Individuals and Non-random Socialmentioning
confidence: 89%
See 1 more Smart Citation
“…Harem groups are relatively unstable in C. sphinx. Thus such association can be explained as an extension of male-female association, as these non-harem males are known to achieve harem status as well (Karuppudurai et al, 2008;Storz et al, 2000), and such an event could have a consequence on the overall relatedness in the harem and the colony and might as well be a reflection of possible cryptic mate choice, a possibility already suggested by Campbell (2008).…”
Section: Relatedness Between Colony Individuals and Non-random Socialmentioning
confidence: 89%
“…Parturition occurs in February to March and again in June to July. Males can undergo transition between harem and non-harem status at varying frequency (Karuppudurai et al, 2008;Swami Doss personal communication). One or more harems along with few solitarily roosting non-harem males in close vicinity make up a colony.…”
Section: Introductionmentioning
confidence: 99%
“…The necklace was secured around the bat's neck, by crimping the sleeved copper ring with long-nose pliers. We have used this type of tagging for various studies and have observed no apparent detrimental effects on bats (Gopukumar et al 2003;Karuppudurai et al 2008). After marking, all individuals were released at the site of capture.…”
Section: Sampling Methods (Mist-netting)mentioning
confidence: 99%
“…Genetic data collected by Storz et al (2001a) over two seasons revealed twofold increase in male mating success contingent on a twofold increase in harem size, indicating high opportunity for sexual selection. However, detailed, long-term behavioural observations reveal that males maintain multiple tents (Paramanantha Swami Doss D. and Vinoth Kumar A. K. personal observation) and the so-called harem male and solitary male strategies ⁄ states also seem to be flexible within and across seasons (Karuppudurai et al 2008;Paramanantha Swami Doss D. personal observation). This suggests an absence of strict mating strategies among males.…”
Section: Introductionmentioning
confidence: 99%